Episodic and Chronic Cluster Headache: Differences in Family History, Traumatic Head Injury, and Chronorisk. Issue 3 (23rd December 2019) - Barloese, Mads C. J.; Beske, Rasmus P.; Petersen, Anja S.; Haddock, Bryan; Lund, Nunu; Jensen, Rigmor H.
Abstract : Objective and Background: The diagnostic criteria of episodic and chronic cluster headache (cCH) were recently modified, yet pathophysiological differences between the two are still unclear. The aim of this cross‐sectional study is to identify and characterize other differences between episodic and cCH. Methods: Data from a retrospective, questionnaire‐ and interview‐based study were analyzed with a focus on associated factors including traumatic head injury (THI), familial history, and change of phenotype. Attack patterns were analyzed using Gaussian and spectral modeling. Results: 400 patients and 200 controls participated. A positive family history was more prevalent in chronic than episodic cluster headache (eCH) (34/146 (23%) vs 33/253 (13%), respectively, P  = .008). A history of THI was more common in patients than controls (173/400 (43%) vs 51/200 (26%), respectively, P  < .0001) and in chronic compared to eCH (77/146 (53%) vs 96/253 (37%), respectively, P  = .004). Patients with a positive family history had a unique diurnal attack pattern with twice the risk of nocturnal attacks as patients who did not report family history. Patients reporting phenotype change had a chronobiological fingerprint similar to the phenotype they had experienced a transition into. A higher attack frequency in chronic patients was the only difference in symptom manifestation across all analyzed subgroups of patients. Conclusions: cCH is associated with a positive family history and THI. In familial CH, a peak in nocturnal chronorisk may implicate genes involved in diurnal‐, sleep‐ and homeostatic regulation. The stereotypical nature of the CH attacks themselves is confirmed and differences between subgroups should be sought in other characteristics.